ANTIPROLIFERATIVE EFFECTS OF PSIDIUM GUAJAVA LEAF EXTRACT ON ORAL SQUAMOUS CARCINOMA CELLS - T RAJAN, SHARADA; N, MALATHI; D, CHAMUNDEESWARI; C, ROSE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Cancer is the major cause of mortality affecting population irrespective of age. Oral cancer is one among the various cancers affecting major population in India. To overcome toxicity of chemotherapy and disfiguration by surgical procedures, researchers are targeting phytochemicals for their anticancer properties. This study evaluates the antiproliferative effects of Psidium guajava leaf extract against OSC cells. Methods: KB cells were purchased from NCCS, Pune. Extract from leaves of P. guajava was prepared with ethanol and evaluated with high-performance thin-layer chromatography (HPTLC). Antiproliferative effects of the extract were assessed with 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl–tetrazolium bromide (MTT) assay and flow cytometry. Results: HPTLC revealed the presence of quercetin in the extract. MTT assay showed decreasing pattern in cell viability with the increasing dose of extract. Flow cytometry revealed the seizing of cycle by the extract. Conclusion: The study results conclude the presence of antiproliferative properties in the leaf extract of P. guajava.